Disappearance of white sharks leads to the novel emergence of an allopatric apex predator, the sevengill shark - Hammerschlag, Neil (Sci Rep, 2019)
Despite global declines of apex predatory sharks, evidence for ecosystem consequences remains limited and debated. This is likely a result of both the logistical difficulties of measuring such processes in marine systems and also due to shifting baselines, whereby the ecosystem changes have occurred prior to monitoring. Between 2000–2018, we conducted standardized monitoring of white shark (Carcharodon carcharias) abundance patterns (N = 6,333 shark sightings) and predatory activity (N = 8,076 attacks on seals) at Seal Island, a Cape fur seal (Arctocephalus pusillus pusillus) colony in False Bay, South Africa. Over the 18-year study, declines in white shark abundance and attack rates were documented between 2015–2018, with anomalous lows occurring in 2017 and 2018. This included prolonged periods of complete white shark absence from Seal Island. The disappearance of white sharks from Seal Island coincided with the unprecedented appearance of sevengill sharks (Notorynchus cepedianus; N = 120 sightings), an otherwise allopatric kelp-associated apex predator in False Bay. We also recorded a sevengill shark attacking a live seal in the absence of white sharks. These data provide empirical evidence for behavioral shifts in an allopatric marine predator following the decline and disappearance of white sharks from a foraging site. This study demonstrates the importance of historical data and long-term monitoring for disentangling ecological consequences of apex predator declines.